As mulheres que Andressa Urach pode ser: celebridades, valores e gênero no Brasil contemporâneo - Maria Lúcia de Almeida Afonso (2019)
This dissertation is dedicated to investigate the values that Andressa Urach has taken on the public scene before and after her religious conversion, and to carry out a comparative study between these two distinct phases of her public life. To do so, we trigger concepts related to the chosen character, which resulted in a link between "celebrity" and "genre", from which we build our analytical grid. Our corpus is constituted of four moments of Andressa's career, having the event of her hospitalization and near-death as a methodological operator for the division of this between a "before" and a "after". From our analysis, we note that the occupation of the public space by women is a historical achievement for the liberation movement of women, but it is not enough. The visibility acquired by women is often accompanied by other processes of oppression, which reveals a malleable facet of the public space. Our findings reveal that although women have been able to break through the delimitation of their bodies into the private space, the place they occupy publicly is still very restricted until today.